1990
DOI: 10.1002/ijc.2910460203
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of colorectal polyps and the effect of polypectomy on occurrence of subsequent cancer

Abstract: To elucidate the natural history of colorectal polyps and to observe the influence of endoscopic polypectomy on the incidence of colorectal cancer, we conducted a retrospective cohort study of all patients who had undergone colonoscopic examination at the Center for Adult Diseases, Osaka, between April 1974 and December 1985. The study subjects consisted of a control group (760 non-polyp patients) and a polyp group (648 polyp patients, including 136 treated by polypectomy at the initial examination). These sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(34 citation statements)
references
References 15 publications
1
31
0
2
Order By: Relevance
“…The characteristic pathophysiology of CRC that involves a slow, latent progression from the first appearance of an adenomatous polyp to the development of CRC has made colonoscopy an ideal screening tool to fight CRC (Muto et al, 1975;Murakami et al, 1990). Offering early detection and colonoscopic excision of precancerous polyps before they transform to CRC (Murakami et al, 1990;Winawer et al, 1993;Bronner et al, 2013), screening colonoscopy has been associated with a substantial decrease in the incidence (Winawer et al, 1993) and mortality rate (Kahi et al, 2009) of CRC in average-risk individuals and FDRs of CRC cases (Lieberman, 1995).…”
Section: Implementation Of Screening Colonoscopy Amongstmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic pathophysiology of CRC that involves a slow, latent progression from the first appearance of an adenomatous polyp to the development of CRC has made colonoscopy an ideal screening tool to fight CRC (Muto et al, 1975;Murakami et al, 1990). Offering early detection and colonoscopic excision of precancerous polyps before they transform to CRC (Murakami et al, 1990;Winawer et al, 1993;Bronner et al, 2013), screening colonoscopy has been associated with a substantial decrease in the incidence (Winawer et al, 1993) and mortality rate (Kahi et al, 2009) of CRC in average-risk individuals and FDRs of CRC cases (Lieberman, 1995).…”
Section: Implementation Of Screening Colonoscopy Amongstmentioning
confidence: 99%
“…Offering early detection and colonoscopic excision of precancerous polyps before they transform to CRC (Murakami et al, 1990;Winawer et al, 1993;Bronner et al, 2013), screening colonoscopy has been associated with a substantial decrease in the incidence (Winawer et al, 1993) and mortality rate (Kahi et al, 2009) of CRC in average-risk individuals and FDRs of CRC cases (Lieberman, 1995).…”
Section: Implementation Of Screening Colonoscopy Amongstmentioning
confidence: 99%
“…Previous studies have suggested that the improvements of diagnostic procedures and the spread of cancer screening have some effects on colorectal cancer incidence. 5,25 The use of colonoscopy and sigmoidoscopy in screening may reduce the risk of colorectal cancer through endoscopic removal of precancerous lesions, or, on the contrary, may produce an increase in colorectal cancer incidence through early detection of cancer. In Miyagi Prefecture, the proportion of screen-detected colon/rectum cancer cases has been increasing since colorectal cancer screening was introduced as a public health program in 1993 (Table 3).…”
Section: Age-period-cohort Modelsmentioning
confidence: 99%
“…The prevention of colon cancer is highly feasible because its precursor lesion, the colonic polyp, is easily recognized and resected at endoscopy, thus preventing advanced cancer (8,11,12,15,30,48,52) . Colonoscopy has been said to be the gold standard for colon cancer screening and prevention because it examines the colon thoroughly, and the precursor lesions can be resected at the same time (13,35,45) .…”
Section: Discussionmentioning
confidence: 99%